Comparison of Extension Personnel and Supervisor Perceptions of Communications Activities - Brittany Bowman; Quisto Settle; Elizabeth Gregory North; Keri Collins Lewis (Journal of Applied Communications, 2018)
Extension is often called the “best-kept secret” having low awareness with the public but high satisfaction with clientele. Extension services nationwide have faced budget cuts, creating a need for the organization to re-evaluate its activities, including how it communicates with its stakeholders. While Extension personnel are the ones who will do most of the communicating, their supervisors impact the personnel’s actions, which means it is important to assess both groups. A survey was conducted with Extension personnel and their supervisors in Mississippi assessing engagement in communications activities and perceptions of those activities, as well as personnel’s preference of professional development activities. Personnel reported higher use, comfort, and importance of more traditional (e.g. making a speech) and written activities (e.g. writing a promotional handout) than media-relations activities (e.g. being interviewed for TV), social media-related activities (e.g. managing a Twitter account), and visual communication activities (e.g. graphic design). Supervisors perceived individual communications activities as less important overall than personnel did, and although supervisor and communication scores for use and comfort/capability were similar for most communication activities, there were noticeable exceptions. Additionally, personnel preferred professional development activities that were hands-on or showing the activities first-hand (e.g. demonstrations and field days). Future research should be expanded to other states, conducted in a case study format to study specific relationships, and involve qualitative components. Extension should ensure clear supervisor-communication dialogue on prioritizing communication activities, provide training on communication activities with low use and comfort, and utilize early innovators who are comfortable using newer communication activities.
Keywords: Cooperative Extension; needs assessment; communications perceptions